2021
DOI: 10.23887/jpepi.v11i1.249
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Core Terhadap Hasil Belajar Matematika Ditinjau Dari Kemampuan Berpikir Kritis Peserta Didik Kelas v Gugus 02 Kuta Utara

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh model Core terhadap hasil belajar matematika ditinjau dari kemampuan berpikir kritis peserta didik. Penelitian ini adalah penelitian eksperimen semu dengan rancangan faktorial 2×2. Populasi penelitian adalah seluruh siswa kelas V sebanyak 233 orang siswa. Sampel pada penelitian ini berjumlah 76 orang siswa. Data kemampuan berpikir kritis dan hasil belajar matematika dikumpulkan dengan tes. Data dianalisis dengan menggunakan analisis Anava AB berbantuan SPSS 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…These results indicate that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. The alternative hypothesis states that there is a significant difference in mathematics learning outcomes between students in the EC 1 class, EC 2 class and the control class [40]- [44]. This significant difference occurs because through PBL and Core learning, students become responsible in mathematics, have confidence in solving math problems, have the initiative in mathematics learning, do not depend on others in mathematics, and are able to solve math problems.…”
Section: Table 4 Two-way Anova Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. The alternative hypothesis states that there is a significant difference in mathematics learning outcomes between students in the EC 1 class, EC 2 class and the control class [40]- [44]. This significant difference occurs because through PBL and Core learning, students become responsible in mathematics, have confidence in solving math problems, have the initiative in mathematics learning, do not depend on others in mathematics, and are able to solve math problems.…”
Section: Table 4 Two-way Anova Resultsmentioning
confidence: 99%
“…Research on the CORE learning model on critical thinking skills has been carried out several times including: the effect of the CORE model on mathematics learning outcomes in terms of critical thinking skills [30], CORE learning through an open-ended approach to improve mathematical critical thinking skills [31], and the effect of CORE learning model on critical thinking skills [32], [33]. Besides, there are studies that discuss the impact of the problem-based learning model on critical thinking skills [34].…”
mentioning
confidence: 99%
“…Model pembelajaran CORE merupakan salah satu strategi pembelajaran kontekstual yang menekankan pada kemampuan berpikir siswa untuk menghubungkan, mengorganisasikan, mendalami, mengelola dan mengembangkan informasi yang didapatnya. Model pembelajaran Connecting Organizing, Reflecting, Extending(CORE) merupakan model yang berpusat pada siswa yang menjadikan siswa belajar bermakna melalui tahapan menghubungkan, mengorganisasikan, merefleksi dan memperluas dengan menggunakan keterkaitan antara sains, lingkungan teknologi dan masyarakat (Kasmita, Ardana, & Gunamantha, 2021;Rohmah & Ulya, 2021). Adapun tahapan model pembelajaran CORE yaitu: Penyampaian proses pembelajaran oleh guru kepada siswa yang menhubungkan konsep lama dengan konsep baru (connecting), siswa dapat menyusun ide-ide untuk memahami materi dengan bimbingan dari guru (organizing), menggali kembali dan menekuni informasi yang diperoleh melalui kegiatan belajar kelompok (reflecting), dan dapat mengembangkan dan memperluas pemgetahuan dengan konsep materi yang didapat melalui pengerjaan tugas-tugas individu sesuai dengan kemampuan yang dimiliki siswa(extending) (Handayani & Surya Kencana No, J. Selatan, 2019;Sari, Suhery, & Effendi, 2020).…”
Section: Pendahuluanunclassified
“…Several studies have shown that the CORE learning model positively influences learning. Research conducted by Kasmita et al (2021) states that there is a significant interaction effect of the CORE Model with critical thinking skills on mathematics learning outcomes. Rasmita et al (2020) concludes that the CORE learning model affects student learning outcomes in solving HOTS questions in class XI students.…”
mentioning
confidence: 99%